2013
DOI: 10.1111/j.1463-1318.2012.03150.x
|View full text |Cite
|
Sign up to set email alerts
|

Prior abdominal open surgery does not impair outcomes of laparoscopic colorectal surgery: a case–control study in 367 patients

Abstract: This large case-control study suggests that PAOS does not affect postoperative outcomes. For this reason, a systematic laparoscopic approach in patients with PAOS, even with midline incision, should be considered in colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Furthermore, all these studies included patients with benign diseases, and none of them reported long-term oncologic outcomes [17e23]. Maggiori et al [22] conducted a large case-control study of 367 patients, but only 105 patients (28.6%) were diagnosed with colorectal cancer. To overcome this potential bias, we conducted a large case-control study specially focused on patients with colorectal cancer and excluded patients with previous laparoscopy or appendectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, all these studies included patients with benign diseases, and none of them reported long-term oncologic outcomes [17e23]. Maggiori et al [22] conducted a large case-control study of 367 patients, but only 105 patients (28.6%) were diagnosed with colorectal cancer. To overcome this potential bias, we conducted a large case-control study specially focused on patients with colorectal cancer and excluded patients with previous laparoscopy or appendectomy.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Whether a laparoscopic approach should be pro posed in patients with recurrent disease, irrespective of the surgical approach used for the index procedure, remains controversial. Indeed, although we reported that a laparoscopic approach did not impair post operative outcomes in patients who had undergone a prior open procedure, 49 Aytac et al 50 suggested that the benefits of a laparoscopic approach in terms of post operative recovery were not maintained in patients after a midline laparotomy. To date, no study has compared the outcomes of laparoscopic management of recurring Crohn's disease with respect to the approach used for the index procedure.…”
Section: Recurrent Crohn's Diseasementioning
confidence: 96%
“…Widespread intraperitoneal adhesions limit intra-abdominal view and create an inadequate working space. This leads to a longer operation time and higher conversion rate (2,3,5). The type of abdominal incision is also an important factor in the success of the laparoscopic procedure (6).…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies about the impact of previous abdominal surgery on laparoscopic colorectal procedures (2)(3)(4)(5). Some of them warn surgeons of the increased risk of conversion or even complication rates in the prior surgery groups (2,3). Others, however, concluded that laparoscopic surgery in patients with previous abdominal surgery was safe and did not have any negative effects (4,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation